(untitled) (Scientiae Studia, 2003)
The aim of this work is to provide an overview of Descartes' role in the debate concerning medical questions, based on his correspondence with Plempius, Regius, Van Beverwick and Van Hogelande. These letters constitute an important record of Descartes' activity together with the doctors, following and discussing the discoveries of his time, and bringing his writings up-to-date. Moreover, this correspondence provides a basis for studying the development of Cartesian medicine in Holland, through some of his interlocutors that were involved with medicine.